The Effect of Digital Literacy and the Spirit of Independence on Entrepreneurial Motivation Among Students - Hafidah, Andi; Idrus , Imriani; Safrillah, Nur Fadhilah; Lutfi, Lutfi (Majapahit Journal of Islamic Finance and Management, 2025)
In the digital era, digital literacy is a very important skill for students, especially in supporting entrepreneurial activities. The spirit of independence is also important which encourages students to take risks and start their own business. This study explores how digital literacy skills and a self-reliant mindset affect students drive to become entrepreneurs.  This quantitative study uses a survey and multiple regression analysis to examine how two independent variables influence the dependent variable. The results of the study based on multiple regression analysis table significance value of digital literacy (X1) of 0.026 <0.05 and the significance value of the spirit of independence (X2) of 0.037 <0.05. The conclusion that digital literacy and the spirit of independence significantly affect student entrepreneurship motivation. The implications of the study indicate the importance of developing digital literacy and the spirit of independence in educational programs to increase entrepreneurial motivation.